ANALISIS DAN PERANCANGAN SISTEM INFORMASI E-LEARNING PADA SMA NEGERI 2 KOTA JAMBI - Simorangkir, Herli; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2019)
The need for e-learning learning materials as a tool for monitoring the teaching and learning process of students so that each subject matter can improve learning outcomes. The consequence of this is that the Jambi City Public High School 2 must be able to improve the quality and quality of the education it carries out. Based on observations and interviews with subject teachers of SMA Negeri 2 Jambi City, the purpose of this study the writer wants to achieve is to analyze and design an e-learning information system at SMA Negeri 2 Jambi City in which there are several methods used in developing this system including Prototype and using system modeling, namely use case diagrams, activity diagrams, and class diagrams. The method used in this research is data collection techniques using observation and interviews. The results obtained were in the form of a web-based E-Learning design at SMA Negeri 2 Jambi City. With e-learning can provide convenience for students to do distance learning or online, so that teachers can conduct monitoring activities even though they are outside of school